Training and Development as Drivers of Organizational Success: Examining the Mediating Effect of Job Satisfaction in the Banking Sector of Karachi, Pakistan - Iqra Muhammad Rafiq,; Hammad Zafar,; Sheikh Muhammad Fakhar-e-Alam, (Dialogue Social Science Review (DSSR), 2025)
The aim of this study is to explore the effects of training and development on the success of an organization, focusing specifically on the mediating role of job satisfaction among employees in some banks located in Karachi, Pakistan. The data will be collected using structured questionnaires completed by employees holding different positions at various banks in Karachi. A total of 120 questionnaires were distributed with a response rate of 102 which were used in the final analysis.The results showed a significant positive correlation between job satisfaction and training as well as development programmes. On top of that, the achievement by an organisation serves as a connection or link between training and development on one hand, and job satisfaction on the other hand; this therefore demonstrates its significance towards enhancing employee productivity while promoting their involvement into organization’s objective. This will lead to increased levels of satisfaction and loyalty amongst participants while stimulating them to achieve better performance at work, thereby boosting overall organizational efficacy The study presents an opportunity to look at the ways in which customized training interventions can help address certain challenges facing the financial sector of Pakistan with a key emphasis on management support and fostering continuous learning culture. Consequently, future studies need to extend their reach and include other variables like employee engagement and organizational commitment so as to gain a deeper understanding in regards to how effective training is within Pakistan’s bank.The link among training and development must be explored because this is critical for success in institutions, especially in the banking sector.